The Role of PI3K in Met Driven Cancer: A Recap - Hervieu, Alexia; Kermorgant, Stéphanie (Frontiers in Molecular Biosciences, 2018)
The Receptor Tyrosine Kinase (RTK) Met, overexpressed or mutated in cancer, plays a major role in cancer progression and represents an attractive target for cancer therapy. However RTK inhibitors can lead to drug resistance, explaining the necessity to develop therapies that target downstream signaling. Phosphatidylinositide 3-kinase (PI3K) is one of the most deregulated pathways in cancer and implicated in various types of cancer. PI3K signaling is also a major signaling pathway downstream of RTK, including Met. PI3K major effectors include Akt and “mechanistic Target of Rapamycin” (mTOR), which each play key roles in numerous and various cell functions. Advancements made due to the development of molecular and pharmaceutical tools now allow us to delve into the roles of each independently. In this review, we summarize the current understanding we possess of the activation and role of PI3K/Akt/mTOR, downstream of Met, in cancer.